2004
DOI: 10.1021/ie049847k
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Correlation Equation between Particle Size and Structure Stability of H−Y Zeolite under Hydrothermal Treatment Conditions

Abstract: The effect of particle size in the range of 0.16−2.01 μm on the hydrothermal stability of H−Y zeolite under hydrothermal treatment conditions similar to those used in FCC processes was investigated. The average particle size of 0.45 μm was found to be the optimum particle size of H−Y zeolite to retain a high percent crystallinity upon hydrothermal treatment. A new correlation was developed by plotting the relative crystallinity (C/C 0) against the reciprocal of the square root of the particle size (d 0) of Y z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The calibration standards were prepared using standard solutions which was certified by the supplier. Three calibration standards (20,40 and 60 mg/l) and a blank solution were used to calibrate the equipment. A linear calibration curve was obtained after calibration.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration standards were prepared using standard solutions which was certified by the supplier. Three calibration standards (20,40 and 60 mg/l) and a blank solution were used to calibrate the equipment. A linear calibration curve was obtained after calibration.…”
Section: Characterizationmentioning
confidence: 99%
“…The particle size measurements were performed by laser beam scattering technique (Coulter LS230). From the particle size distribution (PSD) curves obtained, the sizes, of which 10, 50 and 90 vol.% of the particles in the samples were smaller, could be determined [37][38][39][40]. These particle sizes (by volume) were denoted by d(0.1), d(0.5) and d(0.9), respectively.…”
Section: Characterizationmentioning
confidence: 99%
“…This result was confirmed by Triantafillidis et al [17], who suggested that treatments at relatively high temperatures, or in aqueous solutions with acidic species, lead to the agglomeration of the crystallites that result in the formation of significant macroporous structure. Furthermore, the decrease in the surface area can be explained by the collapse of the zeolite framework and the formation of amorphous silica and alumina, detected also by XRD, 29 Si-MAS-NMR and 27 Al-MAS-NMR, which causes the obstruction of the zeolitic pores. Diffusive reflectance infrared spectra of different samples are given in Figure 3 (A).…”
Section: Characterisationmentioning
confidence: 97%
“…This observation indicates that a large number of extra-framework Si atoms are formed and the regular framework structure is lost. Furthermore, the 27 www.prkm.co.uk exhibited a strong peak at 60 ppm assigned to tetrahedrally coordinated Al species (Al IV ). The study by this technique indicates the creation of the extra-framework aluminium after the dealumination treatment, highlighted by the presence of aluminium atoms in an octahedral environment (δ ≈0 ppm) and pentacoordinated aluminium (δ ≈30 ppm).…”
Section: Characterisationmentioning
confidence: 99%
See 1 more Smart Citation